Perforated gastric ulcer following perforated appendicitis - Kelly Zachariasen; Kimberly Molik (Elsevier, 2020)
Stress ulcers and gastric ulcer perforations are rare in the pediatric population, and there is insufficient evidence to support routine stress ulcer prophylaxis in children. Our case is of a 13-year-old male who presented with appendicitis. He underwent laparoscopic appendectomy and was found to have perforated appendicitis. Postoperatively, he had a prolonged course secondary to ileus and was kept NPO. On postoperative day seven, he acutely worsened with pain and fever. A CT scan was performed to assess for abscess formation and significant free air and fluid was identified without abscess formation. Laparoscopy was performed. He was found to have a large perforated gastric ulcer along the lesser curvature. Conversion to laparotomy was undertaken secondary to poor visualization and significant enteric spillage. The perforation was repaired with a modified Graham patch. This represents a rare case of a perforated stress ulcer in a pediatric patient that was not critically ill and would not have met the most generally accepted indications for stress ulcer prophylaxis in children.